Analysis of Perceptions of Adult Consumers in Surabaya towards the Use of Non-MSG Natural Flavoring - Mahmudi Mahmudi; Bawa Mulyono Hadi; Eureka Milky Setiawan (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Monosodium glutamate (MSG) has long been used as a flavoring in various food products. However, concerns regarding the health impacts of MSG consumption, including sensitivity symptoms such as headaches and high blood pressure, have prompted many consumers to seek healthier alternatives. This study aims to evaluate adults' interest in the use of non-MSG natural flavorings and identify factors that influence this preference. The research method used was a quantitative survey with a sample of 53 adult respondents selected randomly. The research results showed that 56.6% of respondents preferred natural non-MSG flavorings for health reasons, while another 43.4% expressed a desire to use or prefer products made from artificial MSG. Natural alternatives such as anchovies, mushrooms, seaweed and cheese proved popular among respondents. The study concluded that there is significant interest among adults in switching to natural, non-MSG flavorings. Recommendations for food manufacturers include developing products with natural flavors, educating consumers about health benefits, and transparency in product labeling. In this way, manufacturers can meet the needs of a growing market and support healthier eating patterns.